Physician’s Responsibility In Iranian And Islamic Law - Ansari, Reza; Daneshnari, Hamidreza (Opción, 2019)
The medical profession has long been of great importance because of its spe- cialization and dealing with the physical health of humans. However, the sen- sitivity of the medical profession and the technical operations in this profes- sion has always had liabilities for physicians. One of these responsibili-ties is Civil Liability, which, based on Islamic jurisprudence rules and Iranian law and under certain conditions, physicians must compensate a loss. The most important rules of Islamic jurisprudence (Feghh) regarding civil liability in Islamic and Iranian law include: the rule of Prohibition of Detriment, rule of Fraud and Deception, Liability of unlawful Possession, Waste and Causa- tion. Among the opinions of the Sunni jurisconsults on the recognition of civil liability of physicians, they distinguish between the ignorant and the profi- cient physicians; and proficient physicians are scrutinized in terms of Faulty and non-Faulty proficient physicians. In the opinion of Sunni jurisconsults, faulty proficient and ignorant physicians will have civil liability. In the Shi’a jurisprudence, the liability of a faulty and guilty doctor is agreed by the ju- ris-consults, and there is no discrepancy about it. Therefore, it is the duty of the physician, according to the medical convention, to treat the patient from the moment of referral up to the completion of the diagnostic and therapeutic procedures, and apply all the scientific and conventional standards for treat- ing the patient and, if they commit a fault or negligence, they will be liable